PENGEMBANGAN MEDIA WEB INTERAKTIF PADA MATA PELAJARAN IPA KELAS VIII SMP - Siti Zakiyyah Izani; Nofri Hendri; Meldi Ade Kurnia Yusri; Septriyan Anugrah (Jurnal Manajemen Pendidikan, 2026)
Objective: This study aims to develop an interactive web-based learning medium using Scratch on the human respiratory system topic for eighth-grade Natural Science (IPA) students, and to determine its level of validity, practicality, and effectiveness. Methods: This research and development (R&D) study employed the ADDIE model (Analysis, Design, Development, Implementation, Evaluation). The trial involved 24 eighth-grade students of SMP Negeri 25 Padang, two media experts, and one content expert. Data were collected through Likert-scale validation questionnaires, a practicality questionnaire, and a one-group pretest-posttest design, then analyzed using mean scores and a paired t-test. Results: The medium was rated “very valid” by media experts (mean 4.96 and 5.00) and “valid” by the content expert (mean 4.44). The practicality test among students reached a mean of 4.37 (“practical”). The effectiveness test showed t-count of 4.79, exceeding the t-table value of 2.069 (df = 23, α = 0.05), indicating a significant improvement in learning outcomes after using the medium. Novelty: Unlike prior Scratch-based studies that mostly target elementary-level science topics, this study presents a fully web-exported, link-accessible interactive medium specifically developed for a junior high school (SMP) human respiratory system topic, integrating Canva-based visual assets with Scratch’s block-based interactivity and an embedded scoring quiz feature, offering a practical, low-cost, device-flexible alternative for IPA teachers facing limited technology-based teaching resources.